A cold, cold world - Taylor, Elena (Novelist) (Taylor, Elena (Novelist). Sheriff Bet Rivers mysteries, 2024)
A female sheriff tries to fill her late father's boots and be the sheriff her small Washington State mountain town needs as a deadly snow storm engulfs the town, in this dark, twisty mystery.